The Role of Retinopathy Anemia in the Pathogenesis of Retinopathy of Prematurity and the Effect of Erythropoietin Treatment on the Frequency and Severity of the Disease - V. I. Lebedev; L. A. Katargina (Oftalʹmologiâ, 2020)
Premature infants with extremely low birth weight are at high risk of developing severe disabling forms of retinopathy of prematurity. Nonsurgical therapy methods of treatment of retinopathy in prematurity are  ineffective. Taking into consideration the multifactoriality of retinopathy in prematurity, studies aimed at analyzing accessory risk factors aiding the progression of active retinopathy of prematurity and the  development in their pharmacological therapy are relevant for practical healthcare. Effective prevention of retinopathy of prematurity and prevention of severe disabling stages in premature infants at risk require timely diagnosis of the form and severity of anemia. This is the neonatologist’s task. The ophthalmologist should inform the neonatologist about the possibility of developing retinopathy of prematurity in a baby’s eye and about the necessity for diagnostic and remedial measure to treat anemia. The purpose of this study was to assess the impact of early anemia of prematurity on the frequency and severity of retinopathy of prematurity in infants at risk and the effectiveness of its treatment with erythropoietin. The frequency of anemia in preterm risk group (total 1603 children) and its treatment with the degree of prematurity were analyzed. Anemia was manifested in 99–100 % of children with retinopathy of prematurity. The comparative frequency and severity of retinopathy of prematurity was observed in three groups of infants: with extremely low birth weight and gestational age up to 28 weeks of pregnancy (245 children) group I, with gestational age 29–31 weeks of pregnancy (471 children) group II, and more than 31 weeks (581 children) group III. It was found that without treatment in group I retinopathy of prematurity  developed in 100 % of cases and ended with adverse outcomes (IV–V degree of retinopathy of prematurity) in 13.64 %, which is significantly higher (p < 0.01) than after treatment (1.78 %). Similar index was found in groups II and III. Conclusion. We traced the importance of early premature anemia in the pathogenesis of retinopathy of prematurity. It helped us to conclude that the lower the gestational age of the child at the time of birth stronger linked with the dependence of anemia and retinopathy of prematurity. Both of them are associated with the imperfection of the protective mechanisms of preterm infants. Early prescription of erythropoietin significantly improves the clinical course of retinopathy of prematurity and its prognosis.